Pendampingan Membuat Anyaman Untuk Menciptakan Kreativitas Siswa Sekolah Dasar - Asri Putri Anugraini; Firda Alfiana Patricia (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Craft arts will continue to develop and become more interesting and unique as time goes by. The world of art is actually able to create diversity that is of interest to many groups. There are many unique phenomena in the development of woven art or also known as woven. Wicker is basically an inanimate object that can be related to daily activities, especially in the world of architecture or craft products which include interior and exterior aesthetic values. This woven material can be made into a miniature form which can produce various kinds of results such as baskets, mats, bags and crafts. This woven material can be made using various media, for example paper, bamboo, ribbon, etc. Creativity is part of the field of fine arts that can be used in production or creative activities. Various activities in the field of fine arts can provide opportunities to develop the creativity of elementary school children. Creative activities can enable young children to channel their creative talents through several activities, including: drawing; print; stick. Not all children are motivated to channel their talents because there is less encouragement from adults. The cause of low creativity among children in Indonesia is an environment that does not support children to express their creativity, especially the family and school environment. SBDP focuses on students learning skills and arts, this activity can train skills, be creative, actively innovative, for students to work well into the future.